Development and validation of UV Spectrophotometric method for simultaneous estimation of Efonidipine hydrochloride ethanolate and Chlorthalidone in their synthetic mixture - Solanki, Dipika M.; Patel, Dhara V.; Meshram, Dhananjay B. (Drug Analytical Research, 2026)
Efonidipine Hydrochloride Ethanolate and Chlorthalidone is used in management of hypertension and under clinical phase 3 study. The development of quality control method is required for accurate analysis of both drugs. Two simple, precise and economical UV spectrophotometric methods have been developed for the simultaneous estimation of Efonidipine Hydrochloride Ethanolate and Chlorthalidone in their synthetic mixture. Method I is simultaneous equation method (Vierodt’s Method), which is based on measurement of absorption at 251 and 227 nm i.e. λmax of Efonidipine Hydrochloride Ethanolate and Chlorthalidone, respectively. Method II is first order derivative was based on the measurement of absorbance of Efonidipine Hydrochloride Ethanolate measure at 283.2 nm (ZCP of Chlorthalidone) and absorbance of Chlorthalidone measure at 250.8 nm (ZCP of Efonidipine Hydrochloride Ethanolate). Linearity was observed in the concentration range of 6.4-38.4 µg.mL-1 for Efonidipine hydrochloride ethanolate and 2-12 µg.mL-1 for Chlorthalidone using methanol as a solvent. The accuracy of methods was assessed by recovery studies and was found to be within range of 98-102% for both the drugs. Precision of the methods was estimated by repeatability and intermediate precision studies. The % RSD values were found to be less than 2, proving methods were precise. Two methods were compared using F- test. The results were validated statistically as per ICH Q2 R1 guideline and were found to be satisfactory.